A multiresidue analytical method for trace level determination of antibiotics and antiretroviral drugs in wastewater and surface water using SPE-LC-MS/MS and matrix-matched standards. Issue 37 (1st September 2016) - Ngumba, Elijah; Kosunen, Päivi; Gachanja, Anthony; Tuhkanen, Tuula
Abstract : Comparison of matrix-matched and internal standard calibration methods in the analysis of selected antibiotics and antiretroviral drugs in urban waters by SPE-LC-MS/MS. Abstract : An analytical method for simultaneous determination of seven commonly used antibiotics and three antiretrovirals in surface water and urban wastewater at the ng L −1 level has been developed. The method involves concentration and clean-up by solid phase extraction (SPE) followed by identification and quantification by liquid chromatography tandem mass spectrometry (LC-ESI-MS/MS). The use of matrix-matched calibration curves constructed by spiking surface water was evaluated for quantification and compared with the internal standard method using isotopically labelled compounds. The method gave absolute recoveries of 41–116% with most of the compounds having recoveries >50%. The LOQs ranged from 5 to 63 ng L −1 allowing for the determination of the analytes at trace levels in the environmental samples considered. The difference in the quantification results obtained using surface water matrix-matched standards and internal standards was within a ±20% margin. The method provides an affordable and relatively fast alternative with acceptable accuracy and precision. The method was applied to study the occurrence of the target analytes in the surface water of Lake Päijänne and wastewater from the Jyväskylä wastewater treatment plant (WWTP) in Central Finland. All target compounds were detected in the WWTP streams with concentrations ranging between 10 and 570 ng L −1 while low ng L −1 levels were measured for some of the analytes in surface waters. The results institute the need for further monitoring in other WWTP streams and receiving waters as well as improvements of the wastewater treatment process with the aim of minimizing the pharmaceutical load in the effluents.